2018
DOI: 10.1080/00480169.2018.1490214
|View full text |Cite
|
Sign up to set email alerts
|

A survey of canine respiratory pathogens in New Zealand dogs

Abstract: AIMS To determine which of the common canine respiratory pathogens circulate among selected populations of healthy and diseased dogs in New Zealand. METHODS Coagulated blood samples for serology and oropharyngeal swabs for virology were collected from healthy dogs (n=47) and from dogs with acute respiratory disease (n=49). For diseased dogs a convalescent blood sample was also collected 3-4 weeks later. Oropharyngeal swabs were subjected to virus isolation and tested for canine parainfluenza virus (CPIV), cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…Unfortunately, the timing of sample collection was not provided by Knesl et al (2009), but in the current study the lowest seroprevalences were observed in July (29%) and August (32%), which were similar to the 29% reported by Knesl et al (2009). This may also be supported by the fact that 50% of dogs tested as part of another New Zealand-based survey were seropositive for CRCoV (Sowman et al 2018). The number of samples tested in that study was only 93, but, as in the current study, the samples were collected over a period of several months from July 2012 to August 2013.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Unfortunately, the timing of sample collection was not provided by Knesl et al (2009), but in the current study the lowest seroprevalences were observed in July (29%) and August (32%), which were similar to the 29% reported by Knesl et al (2009). This may also be supported by the fact that 50% of dogs tested as part of another New Zealand-based survey were seropositive for CRCoV (Sowman et al 2018). The number of samples tested in that study was only 93, but, as in the current study, the samples were collected over a period of several months from July 2012 to August 2013.…”
Section: Discussionsupporting
confidence: 76%
“…Based on a single cross-sectional survey of 251 dogs, Knesl et al (2009) reported that 73 (29%) dogs were seropositive for CRCoV. In another New Zealand-based study, 47/94 (50%) dogs sampled had antibody to CRCoV (Sowman et al 2018). Some of the dogs affected by ICT seroconverted to CRCoV between acute and convalescent sampling, suggesting that CRCoV infection was associated with the development of disease in those dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease is multi-factorial, and a recent European survey reported that CRCoV, canine pneumovirus and the bacteria Mycoplasma cynos, besides the previously established main causes (mainly CPIV and B. bronchiseptica), all played a role in the disease (Mitchell et al, 2017). To date, the highest prevalence of CRCoV remains in rehoming centres (Erles and Brownlie, 2005;Erles et al, 2003;Mitchell et al, 2017), or other instances where dogs may be cohoused, such as in racing greyhounds (Sowman et al, 2018). Epidemiology is unclear in pet dogs, such as those sampled in our study, but we predict that occasions where many dogs meet…”
Section: Discussionmentioning
confidence: 68%
“…zooepidemics. Although CIRD is the most common, worldwide, its etiology or epidemiology may vary across countries [6,12,18,19,21,28,31].…”
mentioning
confidence: 99%